Effect of annealing process on the heterostructure CuO/Cu2O as a highly efficient photocathode for photoelectrochemical water reduction. (May 2017) - Du, Fan; Chen, Qing-Yun; Wang, Yun-Hai
Abstract: CuO/Cu2 O photocathodes were successfully prepared via simply annealing the electrodeposited Cu2 O on fluoride doped tin oxide (FTO) substrate. They were characterized by X-ray diffraction, scanning electron microscopy (SEM), transmission electron microscope (TEM), UV–vis absorption spectra and X-ray photoelectron spectroscopy (XPS). The results showed that the heterojunction of CuO/Cu2 O was formed during the annealing process and presented the nature of p-type semiconductor. The photocurrent density and photoelectrochemical (PEC) stability of the p-type heterostructure CuO/Cu2 O photocathode was improved greatly compared with the pure Cu2 O, which was greatly affected by annealing time and temperature. The highest photo current density of −0.451 mA/cm 2 and highest stability was obtained via annealing at 650 °C for 15 min (at −0.3 V vs. Ag/AgCl), which gave a remarkable improvement than the as-deposited Cu2 O (−0.08 mA/cm 2 ). This suggested that the CuO/Cu2 O heterojunction facilitated the electron-hole pair separation and improved the photocathode's current and stability. Graphical abstract: Highlights: P-type CuO/Cu2 O photocathode was successfully prepared via a simple method. The maximum photocurrent density of 0.451 mA/cm 2 was obtained. The CuO/Cu2 O heterojunction has excellent photoelectrochemical stability.